On the Empirical Distribution Function of Residuals in Autoregression with Outliers and Pearson’s Chi-Square Type Tests - Boldin, M. V.; Petriev, M. N. (Mathematical methods of statistics, 2018)
We consider a stationary linear AR( p ) model with observations subject to gross errors (outliers). The distribution of outliers is unknown and arbitrary, their intensity is γn −1/2 with an unknown γ , n is the sample size. The autoregression parameters are unknown, they are estimated by any estimator which is n 1/2 -consistent uniformly in γ ≤ Γ < ∞. Using the residuals from the estimated autoregression, we construct a kind of empirical distribution function (e.d.f.), which is a counterpart of the (inaccessible) e.d.f. of the autoregression innovations. We obtain a stochastic expansion of this e.d.f., which enables us to construct a test of Pearson’s chi-square type for testing hypotheses about the distribution of innovations. We establish qualitative robustness of this test in terms of uniform equicontinuity of the limiting level with respect to γ in a neighborhood of γ = 0.